KETAATAN MASYARAKAT DESA BAHU HALMAHERA SELATAN TERHADAP LARANGAN PERKAWINAN BULAN MUHARRAM PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Sahrul, Rudi Sahrul; Abbas, Abdul Haris; Giling, Mustamin (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2024)
AbstractThe people of South Halmahera, especially Bahu Village, have a prohibition on marriage in the month of Muharram, they are not allowed to hold weddings, the prohibition on marriage is due to several influencing factors, the customary rules that prohibit marriage in the month of Muharram are a fear factor, the community believes that if they violate tradition they will experience disaster, such as the wedding not going smoothly, the family is not harmonious, the family economy will decline and it will be difficult to restore it, and the psychological factor is that people who violate the customary rules of marriage during the month of Muharram often have arguments in their households, there is no peace and discomfort. Meanwhile, in the sociological theory of Islamic law, the factors that influence the prohibition of marriage in the month of Muharram must also be seen from a historical, social and religious perspective. On the other hand, the tradition of prohibiting marriage during the month of Muharram is maintained because the custom of using traditional figures as role models is inherited from ancestors. The aim of the research is to determine the community's understanding of the custom of prohibiting marriage in the month of Muharram in Bahu1 Village, to find out the factors that influence community compliance with the custom of prohibiting marriage in the month of Muharram, to find out the community's obedience to the custom of prohibiting marriage in the month of Muharram from an Islamic Legal Sociology Perspective. The data collection method is through surveys, documentation and in-depth interviews with the community related to the research objectives. Data analysis is carried out by data reduction and data presentation, namely the process of compiling complex information in a systematic form so that it is simpler and its meaning can be understood. Results and discussion, consider factors that show that the obedience of the Bahu Village community to the prohibition of marriage in the month of Muharram can be understood as the result of a complex interaction between social, cultural and Islamic legal factors. Demonstrates the importance of understanding the local context and social dynamics in analyzing behavior and compliance with the prohibition on marriage in the month of Muharram, which is still considered 'urf shahih, carried out by the people of Bahu Village Keywords: Prohibition of Marriage in the Month of Muharram, Sociological Perspective, Islamic Law